Contribucion al conocimiento de Euzopher pinguis (Haworth, \{1811\})(Lep.: Pyralidae), plaga del olivo - Duran, J.M.=700 1 Alvarado, A.; Serrano, A.; De la Rosa, A.
(Es, En)
ilus., 14 ref.
Keywords: PYRALIDAE; INSECTA; OLEA EUROPAEA; DINAMICA DE LA POBLACION; CONTROL QUIMICO; FENITOTRION; ACEITE; ESPAÑA; EUZOPHERA PINGUIS